Pengaruh Social Media dan Event Marketing terhadap Minat Beli di Pyukanau Official - Nisya Firdailla; Hanni Haerani (Neolectura, 2021)
The purpose of this study was to determine the effect of Social Media and Event Marketing on the Buying Interest of fashion products. The method used is quantitative, correlation looks for the relationship between variables. In this study, the population is Pyukanau Official Instagram followers, totaling 544 using the Slovin formula, 100 respondents are needed. Sampling using purposive probability sampling technique by distributing questionnaires through Google Form. The results of testing using IBM SPSS Statistics version 26.0 are R2 value 0.867 and R2 coefficient 0.752 or 75.2%. Social media has an effect on buying interest with a t value of 4,697 > t table 1,984, event marketing has an effect on buying interest with a t value of 5,824 > t table 1,984, and simultaneously between social media (X1), event marketing (X2), there is an influence significant positive on buying interest (Y) at Pyukanau Official with a value of Sig 0.000b (p < 0.05).